Sexual harassment among male and female public accountants: an exploratory study - Ngo, Fawn T. (Deviant behavior, 2022)
There is a dearth of empirical studies examining sexual harassment within the accounting industry and that which does exist tends to focus exclusively on female victims. Employing six individual-level characteristics and five organizational-level characteristics, this study examines the prevalence and nature of workplace sexual harassment among a sample of male and female certified public accountants. This study also assesses whether the correlates of sexual harassment differ by gender. Results indicate that female respondents have greater risks of encountering sexual harassment relative to male respondents. Further, two organizational-level measures, management’s view on workplace sexual harassment and whether the firm has made adequate provisions to deal with the issue, also emerged as significant predictors of workplace sexual harassment. Limitations and suggestions for future research are discussed.